A novel cryptic CBFB-MYH11 gene fusion present at birth leading to acute myeloid leukemia and allowing molecular monitoring for minimal residual disease - P.J. Poddighe; M.A. Veening; M.B. Mansur; A.H. Loonen; T.M. Westers; P.A. Merle; J.W. Wessels; V. de Haas; W.A. Kors; S.L. Bhola; M.J. Wondergem; A.M. Ford; et al. (Elsevier, 2018)
Acute myeloid leukemia (AML) with the inv(16)/t(16;16) karyotype is associated with a favourable prognosis, showing longer periods of complete remission and high overall survival rates. Here we report a four year old girl, who presented with pallor, a history of viral infections and pancytopenia, an abnormal karyotype, but initially no signs of leukemia. After one month, molecular diagnostics revealed a rare CBFB/MYH11 fusion variant transcript type S/I, leading to the diagnosis of CBF AML. Additional FISH confirmed the presence of a cryptic CBFB/MYH11 fusion. We developed a nested PCR test for the CBFB/MYH11 fusion gene transcript S/I to monitor this patient for minimal residual disease. Eleven months after complete remission this transcript was still absent in peripheral blood samples.Because at presentation this girl had no clinical signs of leukemia, but showed an abnormal karyotype with a cryptic CBFB-MYH11-fusion, we investigated whether this fusion was already present at birth. Therefore, the DNA fusion junction was cloned from diagnostic DNA and the patient-specific sequence was used to investigate the neonatal blood spot. Remarkably, the type S/I transcript of CBFB/MYH11 was present in the neonatal blood spot, most likely being the first hit in leukemogenesis. Keywords: AML, CBFB-MYH11 fusion gene, Cytogenetics, RT-PCR, MRD, Neonatal blood spot